The role of immunoglobulin D in autoimmunity. (Research'eu results magazine)
'Systemic lupus erythematosus' (SLE) is an inflammatory autoimmune disease associated with increased levels of 'immunoglobulin D' (IgD). Understanding the connection between the two will lead to improved therapies for SLE.